A novel nanostructured biosensor for the detection of the dust mite antigen Der p2 - Tsai JJ (Dove Medical Press, 2011)
Jaw-Ji Tsai1, I-Jiuan Bau2, He-Tsing Chen2, Yu-Ta Lin3, Gou-Jen Wang2,31Department of Medical Education and Research, Taichung Veterans General Hospital, Taichung, Taiwan; 2Graduate Institute of Biomedical Engineering, 3Department of Mechanical Engineering, National Chung-Hsing University, Taichung, TaiwanAbstract: The group 2 allergen, Der p2, has been reported to activate innate toll-like receptors (TLRs) on respiratory epithelial cells and thus aggravate respiratory diseases. In this study, a highly sensitive nanostructured biosensor based on a 3D sensing element with uniformly deposited gold nanoparticles is proposed for the detection of the dust mite antigen Der p2. The barrier layer comprises an anodic aluminum oxide (AAO) film which is used as the template in this highly sensitive nanostructured biosensor. Simple electrochemical deposition without reducing agent and stabilizer was enough to uniformly synthesize gold nanoparticles on the surface of the barrier layer. The size and the distribution density of the nanoparticles can be well controlled by the applied potential during electrochemical deposition. Following this procedure, the dust mite monoclonal antibodies (IgG) were then immobilized through the 11-MUA (11-mercaptoundecanoic acid), (1-ethyl-3-(3-dimethyl-aminopropyl)-carbodiimide)/(N-hydroxysuccinimide) self-assembled monolayer approach for the dust mite antigen Der p2 detection. The detection limit of the proposed 3D gold nanoparticle-based nanostructured biosensor was examined using electrochemical impedance spectroscopy analysis and found to be 1 pg/mL. The dynamic range was found to be 5 µg/mL. The proposed nanostructured biosensor would be useful for fast detection of rare molecules in a solution.Keywords: anodic aluminum oxide template, gold nanoparticles, nanostructured biosensor, Der p2 detection, electrochemical impedance spectroscopy analysis